Tetrabutylammonium Valinate Ionic Liquid Grafted Nano-SiO2: A Novel Heterogeneous and Reusable Catalytic System for the Synthesis of Naphthopyran Derivatives Under Solvent-Less Condition - Verma S.; Verma S.; Agrwal A.; Kasana V. (My University, 2025)
In the present study, we have synthesized TBAVIL@nano-SiO2 as a novel heterogeneous catalytic system by using tetrabutylammonium valinate ionic liquid (TBAVIL) and silica nanoparticles. The designed catalytic system is used for the preparation of naphthopyran derivatives by reacting substituted aromatic aldehyde, β-naphthol, and malononitrile in one pot system without the addition of solvent and co-catalyst. This method affords excellent yield (85–96%) of all the products with less reaction time (7–42 min). The catalyst reusability is also checked up to five cycles and found to have excellent activity up to three cycles. © 2023 Taylor & Francis Group, LLC.